2013
DOI: 10.3109/09273948.2013.801988
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Contamination of Needles Used for Intravitreal Injections: Comparison between 27-gauge and 30-gauge Needles

Abstract: The results suggest that the needle bore size seems not to be a risk factor for contamination during IVT injection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
0
7
0
1
Order By: Relevance
“…The results suggested that the needle bore size seemed not to be a risk factor for contamination during IVT injection (Tufan et al. ). Fortunately in our study, we had no occurence of endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…The results suggested that the needle bore size seemed not to be a risk factor for contamination during IVT injection (Tufan et al. ). Fortunately in our study, we had no occurence of endophthalmitis.…”
Section: Discussionmentioning
confidence: 99%
“…There is general agreement between IVI guidelines that injections should be made through the pars plana, between 3.5 and 4 mm from the limbus [2, 132]. A more posterior injection site potentially increases the risk of retinal detachment, while a more anterior approach increases the risk of traumatic cataract formation or hemorrhage, if the ciliary body is pierced.…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 99%
“…Regarding EO risk after IVI, needle size does not seem to be a relevant factor [131]. Thirty-gauge or thinner needles are recommended for liquid injections [132], whereas larger needles should be used when necessary, as for example for Ozurdex® injections. Expert panel guidelines suggest using any needle length from 13 to 18 mm [2, 115].…”
Section: Peri- /Injection Management In Intravitreal Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Что касается диаметра инъекционной иглы, то в рекомендациях отмечается возможность применения игл диаметром от 27 до 33 G, но для введения жидкостей предпочтительнее иглы диаметром 30 G и тоньше [16,35]…”
Section: Discussionunclassified